Forest succession improves the complexity of soil microbial interaction and ecological stochasticity of community assembly: Evidence from Phoebe bournei-dominated forests in subtropical regions - He, Gongxiu; Peng, Tieshuang; Guo, Yi; Wen, Shizhi; Ji, Li; Luo, Zhong (Frontiers in Microbiology, 2022)
Forest succession is a central ecological topic because of the importance of its dynamic process for terrestrial ecosystems; however, very little is currently known about community assembly and interaction of soil microbial community along a forest successional trajectory, particularly the microbial community dynamic in contrasting seasons. To bridge these knowledge gaps, we studied the soil bacterial and fungal community compositions, assemblages and co-occurrence networks in a well-established successional gradient of Phoebe bournei-dominated forests, which spans about 65 years of forest development in the subtropical region. The Illumina MiSeq sequencing of 16S and ITS genes were employed soil bacterial and fungal community composition and diversity, respectively. The relative abundance and α diversity of soil bacteria and fungi showed a differential trend over forest succession. The dominant fungal phyla (Basidiomycota and Ascomycota) changed more frequently than the dominant bacterial phyla (Proteobacteria, Acidobacteriota, and Actinobacteriota), indicating soil fungi exhibit a more sensitive association with forest succession compared with bacteria. The variation of soil microbial community induced by forest succession was significantly affected by soil total phosphorus, dissolved organic carbon contents and pH. Besides the deterministic processes, the stochastic processes mainly dominated the community assembly of soil microbial communities. The relative importance of stochasticity in soil fungal communities increased in the later stages. Particularly, dispersal limitation and drift account for a large proportion of community assembly of bacterial and fungal communities, respectively. In addition, the co-occurrence networks of soil microbial communities were more complex as succession proceeds. Soil bacteria and fungi exhibited more competition and cooperation along a forest successional gradient. Collectively, our findings suggest that forest succession improves the complexity of soil microbial interaction and ecological stochasticity of community assembly in Phoebe bournei-dominated forests, providing important insights into the relationship between microbial community and forest succession.